A combination of blind source separation and impulsive chaos synchronisation for encryption. (1st January 2013) - Chen, Wei-Ching; Yuan, John
In this paper, a secure communication scheme is proposed in which both blind source separation (BSS)- and chaos-based cryptographic techniques are utilised. In the transmitter, the message signal is mixed with white noise to form two mixed signals. One of the mixed signals is directly transmitted to the receiver, while the other mixed signal is further interfered with using a chaotic signal before being transmitted to the receiver. Impulsive synchronisation is utilised to reproduce the chaotic signal and is incorporated with a modified independent component analysis at the receiver end in order to retrieve the message signal. The key space, key selection rules and a security analysis are discussed. A cryptanalysis study is presented to show that the proposed scheme is immune to some attacks. Simulation results show that this scheme has an enhanced level of encryption security.